Clinical Manifestations of Acute COVID-19 in Previously Healthy Pediatric Patients Diagnosed by Rapid Antigen Screening in a Community-Based, Outpatient Primary Care Pediatrics Practice - Stanley Calderwood; Eduardo. L. Montoya; Mandeep Singh Brar (Children)
Background: The PediCenter and Niles Children’s Clinic provide pediatric primary and urgent care services in central California. We remained open throughout the COVID-19 pandemic, providing scheduled well child-care and sick visits. Methods: Beginning in September 2020, we implemented a COVID-19 screening program. Screening was performed on all patients presenting for care and was made available to patients requiring testing for any purpose. Herein, we provide results from that program, including a description of clinical characteristics of COVID-19 in our patients. Results: Key findings: A total of 11,649 COVID-19 antigen screening tests were performed (age range 0.1 to 17.0, mean 8.7, SD 4.5). In total, 1560 pts. (13.4%) tested positive. Among these, 665 (43%) were asymptomatic, 560 (36%) had mild disease, 318 (20%) had moderate disease, and 17 (1%) had severe disease. No critical cases or transfers to the emergency room were reported. Younger patient age was associated with an increased severity of illness, as was time from the onset of the pandemic. A total of 4446 patients reported no symptoms at the time of screening, 15% of whom tested positive. In total, 7203 patients reported symptoms at the time of testing. Among these, 87.6% tested negative and 12.4% tested positive. Disease severity was similar between these two groups. COVID-19 is generally a mild respiratory tract infection in healthy children. Conclusions: Screening is effective in identifying cases, including asymptomatic cases. Statistical models further revealed associations between patient age, time from the onset of the pandemic, and disease severity.